Writing Process Approach and Its Effect on Student' Writing Anxiety and Performance - Kurniasih Kurniasih; Fitri Awaliyatus Sholihah; Atik Umamah; Ika Hidayanti (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This study aims at investigating the effect of the process approach on student writing anxiety and performance. Teachers should find ways to cope with anxiety as it is known as the negative predictor of students' writing performance. Fifteen students participated in this study. They were assigned to write an argumentative essay under the topic